RESOLUSI KONFLIK PERAMBAHAN TAMAN NASIONAL LORE LINDU DI DONGI-DONGI PROPINSI SULAWESI TENGAH - DODY, DODY ([Yogyakarta] : Universitas Gadjah Mada, 2015)
The process of land conflict management in Dongi-dongi as a part of Lore Lindu National Park had been getting occurred a long time since 2001. The land conflict was not only structural-vertical characteristic but was also horizontal one because of different perspective of the stakeholders managing the forest area. Based on Furlong’s model boundary, it was known that the land conflict occurred caused the boundary (rules) had been challenged, threatened or circumvented/ignored thus requiring intervention of the Lore Lindu National Park Authority that had the jurisdiction by using zoning review. Connected to the zoning review of Lore Lindu National Park including Dongi-dongi itself, this research used qualitative method to describe conflict resolution mechanisms and initiatives by using governance in ordered to construct a collaboration among stakeholders expected to generate an adaptive rule that synergize between the needs of people and conservation.